Abraham Lincoln's Wilderness Years : Collected Works of J. Edward Murr - Murr, J. Edward (John Edward), 1898-1960 (Book collections on Project MUSE., 2022)
"Abraham Lincoln spent a quarter of his life--from 1816 to 1830, ages 7 to 21--learning and growing in southwestern Indiana. Despite the importance of these formative years, Lincoln rarely discussed this period, and with his sudden, untimely death in 1865, mysterious gaps appear in recorded history. In "Abraham Lincoln's Wilderness Years," Joshua Claybourn collects and annotates the most significant scholarship from J. Edward Murr, one of the only writers to cover this lost period of Lincoln's life. A Hoosier minister who grew up with the 16th president's cousins, Murr interviewed locals who knew Lincoln. Part I features selected portions of Murr's book-length manuscript on Lincoln's youth, published here for the first time. Part II offers a series by Murr on Lincoln's life in Indiana, originally printed in the "Indiana Magazine of History." Part III reveals letters between Murr and U.S. Senator Albert J. Beveridge, a prominent historian, about Beveridge's early manuscript of the biography Abraham Lincoln, 1809-1858. Of all Lincoln's biographers, none knew his boyhood associates and Indiana environment as well as Murr, whose complete Lincoln research and scholarship have never been published--until now. "Abraham Lincoln's Wilderness Years" preserves and celebrates this important source material, unique for studying Lincoln's boyhood years in Indiana"--